Modele ze zmiennymi ukrytymi w segmentacji rynku - Bąk, Andrzej (Latent Variables Models in Market Segmentation, 2007)
Latent variable models account for heterogeneity of consumer at the group (segment) level. Therefore they may be used as a tool of market segmentation. Model estimation involves, among others, estimation of the number and size of individual segments. The paper presents basic feathers of latent variables models and the benefits of their use in market segmentation on the marketing research field. Then it presents the problems connected with those models which should be the subject of further research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (14); 2007; nr 1169, s. 411-419